2021
DOI: 10.1111/tbed.14184
|View full text |Cite
|
Sign up to set email alerts
|

The seroprevalence of the newly identified porcine circovirus type 4 in China investigated by an enzymed‐linked immunosorbent assay

Abstract: Porcine circovirus 4 (PCV4) is the fourth porcine circovirus newly identified in China, and it could be detected in diseased and healthy pigs. To date, the prevalence of PCV4 DNA in pig herds has been investigated in many provinces from both China and Korea, with positive rates varied from 3.28% to 25.4% in samples from different regions. However, up to now no serological data have been reported to evaluate the prevalence of PCV4 in pig herds. In this study, an indirect anti-PCV4 IgG enzyme-linked immunosorben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…In a serological survey of 1790 serum samples collected from pigs in 17 provinces of China between 2008 and 2020, overall seroprevalence of PCV4 was 43.97% [ 5 ]. PCV4 Rep-specific antibodies were detected in sera from pigs of various ages, with the highest prevalence (67.8%) in sows, and the earliest evidence from a sample collected in 2008 [ 5 ].…”
Section: Epidemiology Of Pcv4 and Clinical Diseases Associated With T...mentioning
confidence: 99%
See 2 more Smart Citations
“…In a serological survey of 1790 serum samples collected from pigs in 17 provinces of China between 2008 and 2020, overall seroprevalence of PCV4 was 43.97% [ 5 ]. PCV4 Rep-specific antibodies were detected in sera from pigs of various ages, with the highest prevalence (67.8%) in sows, and the earliest evidence from a sample collected in 2008 [ 5 ].…”
Section: Epidemiology Of Pcv4 and Clinical Diseases Associated With T...mentioning
confidence: 99%
“…In a serological survey of 1790 serum samples collected from pigs in 17 provinces of China between 2008 and 2020, overall seroprevalence of PCV4 was 43.97% [ 5 ]. PCV4 Rep-specific antibodies were detected in sera from pigs of various ages, with the highest prevalence (67.8%) in sows, and the earliest evidence from a sample collected in 2008 [ 5 ]. In another serological survey of 1048 pig serum samples collected from Jiangsu province of China between 2018 and 2021, 3.44% of samples had PCV4 Cap-specific antibodies [ 27 ].…”
Section: Epidemiology Of Pcv4 and Clinical Diseases Associated With T...mentioning
confidence: 99%
See 1 more Smart Citation
“…The most recently reported PCV, namely, PCV4, was first identified in Chinese farmed pigs with severe clinical disease in 2019 [ 5 ]. Thereafter, several groups have conducted epidemiological investigations on PCV4 and found that PCV4 also exists widely in pigs [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Kim et al found that the positive rates of PCV4 in individual pig samples and at the farm level were 39.3% and 45.7%, respectively [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang, Bai, et al, 2020). Ge et al (2021) performed a serological survey on PCV4 using serum samples collected from 17 provinces of China, and the results showed that the positive rates ranged from 0% to 83.33%, which indicated the widespread of PCV4 in China. Jiangsu province is located at the Yangtze River, an important pig producing area in China.…”
Section: Introductionmentioning
confidence: 99%